Ultrasonographic Assessment of Uterine and Ovarian Structural Changes during the Menstrual Cycle in Relation to Hormonal Variations - Shambhavi Soni; Akash Bansal; Aishwarya Srivastava; Amit Kumar Srivastava (Journal of Pharmacy and Bioallied Sciences, 2025)
Background: The menstrual cycle involves complex hormonal interactions that induce structural and functional changes in the uterus and ovaries. Ultrasonographic imaging offers a noninvasive means to assess these variations. This study evaluates uterine and ovarian structural changes during different phases of the menstrual cycle and correlates them with hormonal fluctuations. Materials and Methods: A prospective observational study was conducted on 50 women aged 20–35 years with regular menstrual cycles. Participants underwent transabdominal and transvaginal ultrasonography during the follicular, ovulatory, and luteal phases. Hormonal levels of estrogen, progesterone, and luteinizing hormone (LH) were assessed using serum samples collected at each phase. Measurements included endometrial thickness, ovarian follicle diameter, and corpus luteum dimensions. Results: Endometrial thickness showed a progressive increase from the follicular phase (4.5 ± 0.8 mm) to the luteal phase (10.2 ± 1.1 mm, P < 0.05). The dominant follicle diameter peaked during ovulation (18.5 ± 2.0 mm, P < 0.01) and was replaced by the corpus luteum in the luteal phase (14.0 ± 1.5 mm, P < 0.05). Hormonal analysis revealed a significant rise in estrogen during the follicular phase (mean: 180 ± 20 pg/mL), LH surge at ovulation (mean: 25 ± 5 IU/L), and elevated progesterone levels during the luteal phase (mean: 15 ± 3 ng/mL). Conclusion: Ultrasonographic assessment effectively demonstrates dynamic structural changes in the uterus and ovaries during the menstrual cycle. These changes correlate significantly with hormonal variations, providing valuable insights into reproductive health and aiding in the diagnosis of menstrual disorders.